Building on the Theory of the Comfort Zone of Gender Inequality: Analysis of Survey Findings - Osondu-Oti, Adaora; Abodunrin, Jane (The Gender Truth Journal, 2025)
Despite centuries of efforts to end gender inequality (GI), the world is still not on track to achieve gender equality by 2030. No country has achieved gender parity, and it is not likely that an additional 15 years at the end of 2030 (what can be called “Progressive Sustainable Development Goals – P-SDGs”) will do the magic by 2045. The World Economic Forum Global Gender Gap report 2024 made it clear that at the current rate of progress, full gender parity will not be reached until the year 2158. Based on the foregoing, the central argument of this paper is that gender inequality has persisted because it is a comfort zone for men. It is a place where men prefer to stay because of the benefits to them, regardless of the consequences for the disadvantaged group (women). Two main research questions, among other questions, addressed in this paper are: is gender inequality a comfort zone for men, and if yes, what is your understanding of gender inequality in line with the comfort zone thesis? Using survey data, this paper builds on the theory of the comfort zone of gender inequality, which was first advanced by Osondu-Oti (2024) in an article titled “The Comfort Zone of Gender Inequality: A Reflection.” Findings from this survey affirm that gender inequality is a comfort zone for men, especially those with “authoritative power”- the main beneficiaries of gender inequality. In line with the comfort zone thesis, findings from the survey show that gender inequality is a rational choice because of men’s fear of losing power and authority in both private and public domains. Gender inequality also puts men in an advantageous position where they feel more at ease and in control, and being that it is familiar terrain, they are reluctant to leave their comfort zone. It is therefore recommended that more awareness be created about gender inequality being a comfort zone for “men,” so that advocates of gender equality, including feminist movements and scholars, can engage in a stronger push for equality. This is because these men are less likely to be committed to the struggle for gender equality, since they are in their “hegemonic palace” with the comfort therein. In addition, more practical commitments by organisations to the empowerment of women and girls are needed more than ever, especially investing in girl-child education. Education is power, and it remains the first and a crucial step that will guarantee more placement of women in positions of authority in the years to come, as authoritative power is still less available to women.